Asset allocation : from theory to practice and beyond - Kinlaw, William; Kritzman, Mark P.; Turkington, David, 1983- (John Wiley & Sons, Inc., 2021)
"Investors have access to a vast array of assets with which to form portfolios, ranging from individual securities to broadly diversified funds. The first order of business is to organize this massive opportunity set into a manage- able set of choices. If investors stratify their opportunity set at too granular a level, they will struggle to process the mass of information required to make informed decisions. If, instead, they stratify their opportunity set at a level that is too coarse, they will be unable to diversify risk efficiently. Asset classes serve to balance this trade-off between unwieldy granularity and inefficient."--